The impact of immunoglobulin in acute HIV infection on the HIV reservoir: a randomized controlled trial. Issue 10 (18th July 2017) - Tiraboschi, J; Ray, S; Patel, K; Teague, A; Pace, M; Phalora, P; Robinson, N; Hopkins, E; Meyerowitz, J; Wang, Y; Cason, J; Kaye, S; et al.
Abstract : Objectives: Antiretroviral therapy (ART) during acute HIV infection (AHI) restricts the HIV reservoir, but additional interventions are necessary to induce a cure. Intravenous immunoglobulin (IVIG) is not HIV‐specific but is safe and temporarily reduces the HIV reservoir in chronic HIV infection. We present a randomized controlled trial to investigate whether IVIG plus ART in AHI reduces the HIV reservoir and immune activation compared with ART alone. Methods: Ten men with AHI (Fiebig II−IV) initiated ART (tenofovir, entricitabine, ritonavir boosted darunavir and raltegravir) at HIV‐1 diagnosis and were randomized to ART alone or ART plus 5 days of IVIG, once virally suppressed (week 19). Blood samples were evaluated for viral reservoir, immune activation, immune exhaustion and microbial translocation. Flexible sigmoidoscopy was performed at weeks 19, 24 and 48, and gut proviral DNA and cell numbers determined. Results: IVIG was well tolerated and no viral blips (> 50 HIV‐1 RNA copies/mL) occurred during IVIG therapy. From baseline to week 48, total HIV DNA in peripheral blood mononuclear cells (PBMCs) (cases: −3.7 log10 copies/10 6 CD4 cells; controls: −3.87 log10 copies/10 6 CD4 cells) declined with no differences observed between the groups ( P = 0.49). Declines were observed in both groups from week 19 to week 48 in total HIV DNA in PBMCs ( P = 0.38), serum low copy RNA ( P = 0.57) and gut total HIV DNA ( P = 0.55), but again there were no significant differences between arms. Biomarkers of immune activation, immune exhaustion and microbial translocation and the CD4:CD8 ratio were similar between arms for all comparisons. Conclusions: Although safe, IVIG in AHI did not impact total HIV DNA, immune function or microbial translocation in peripheral blood or gut tissue.